Suspension of Insurers' Dividends as a Response to the Covid-19 Crisis: Evidence from Equity Market - Petr Jakubik; Saida Teleu (Charles University in Prague, Institute of Economic Studies (IES), 2021)
The recent Covid-19 outbreak with significant increase of global uncertainties poses many challenges for financial sectors. Many supervisors took the measures aiming to safeguard resilience of financial institutions by requesting postponements any dividend distributions until uncertainties about further development will be reduced. In this respect, the European Insurance and Occupational Pensions Authority issued on Thursday 2nd April 2020 a statement requesting (re)insurers to suspend all discretionary dividend distributions and share buy backs aimed at remunerating shareholders. Although this should have a positive impact on the overall financial stability of the sector, it could also negatively influence insurers' equity prices. Hence, this paper empirically investigates this potential effect using an event study methodology. Despite negative drops were observed in some cases, the obtained empirical results suggest that they were not statistically significant for the overall European insurers' equity market when considering the event windows covering a few days after the statement was published.
Keywords: G22; G28; G35; G01; 330; European insurance sector; suspension of dividend distributions; event study; EIOPA statement; equity market